A Critical Study on the Fundamentals of Masalih and Mafasid’s Attainments in the light of Sharia’s Objectives.: مقاصد شریعہ میں مصالح اور مفاسد کی پہچان کے طرق و ضوابط کا تنقیدی مطالعہ - Hasan Shah, Muhammad Mahmood ul; Tayyabi, Dr. Anwarullah; Shah, Dr. Muhammad Ahmad (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Islam is a complete code of life and a religion for all humankind. Its injunctions invite humanity to balance their approach towards themselves and all living and non-living things in the universe to preserve the ultimate objective of existence and an opportunity to succeed in the world and the hereafter. Its very commandments lead towards benefits (Masalih) and prevent from harms (Mafasid) in every sphere of life and the afterlife and have a simple purpose to provide comfort peace, respect, justice and most importantly a loving but submissive relationship with Almighty Allah. It’s a daunting task to grasp the actual objectives of Islamic Sharia and the most difficult part is to understand the basic sources and principles of recognitions of Masalih and Mafasid. Ergo, this article deals with the significance of reason and its logical tools to highlight and show the Sharia’s answers of the contemporary issues as well as remaining instruments of identifications of Masalih and Mafasid in the light of the Sharia’s objectives for a successful human life and the betterment of the whole world and the afterworld.